A case study on perceived waiting time, customer satisfaction and repatronization at Kentucky Fried Chicken (KFC), i-City, Section 7, Shah Alam / Wan Nur Farhana Wan Sazali and Maisarah Mazlan - Wan Sazali, Wan Nur Farhana; Mazlan, Maisarah (Faculty of Hotel and Tourism Management, 2013)
Quick Service Restaurants (QSR) are restaurants that offer convenience and value services with specific characteristic both by their fast food cuisine and minimal table services. However, the service presented at many of QSR outlet are below the established standard of operation as well as not providing the least of waiting time for their customer. Previous studies have widely shown the effect of waiting time on customer service satisfaction and re-patronization. The aim of this study is to determine the QSR outlets perceived waiting time that associated with customer satisfaction and re-patronization especially in one of the famous quick service outlet i.e. Kentucky Fried Chicken (KFC), located in i-City section 7, Shah Alam, Selangor. Customers who dined in KFC outlet were solicited to fill up a set of questionnaire using self-administered questionnaire. The study framework of this case study is based on Theory of Reasoned Action by Ajzen and Fishbein (1980) which has been broadly applied in various researches in consumer behavior. The major findings of this study show that queuing design have an impact on re-patronization. Results of this study will help the QSR manager and management to understand the behavior of their customers, and take appropriate counteractive action to survive in this very aggressive industry.